Evaluating the Efficacy of Therapies in Patients With Coronavirus Disease 2019. (21st August 2020) - Lin, Dan-Yu; Zeng, Donglin; Eron, Joseph J
Abstract: There is a proliferation of clinical trials worldwide to find effective therapies for patients diagnosed with coronavirus disease 2019 (COVID-19). The endpoints that are currently used to evaluate the efficacy of therapeutic agents against COVID-19 are focused on clinical status at a particular day or on time to a specific change of clinical status. To provide a full picture of the clinical course of a patient and make complete use of available data, we consider the trajectory of clinical status over the entire follow-up period. We also show how to combine the evidence of treatment effects on the occurrences of various clinical events. We compare the proposed and existing endpoints through extensive simulation studies. Finally, we provide guidelines on establishing the benefits of treatments. Abstract : To enhance clinical relevance and improve statistical power, we propose to evaluate the efficacy of therapies in COVID-19 patients by considering the entire trajectory of clinical status and combining the evidence of treatment effects on the developments of important clinical events.